2021
DOI: 10.11124/jbies-20-00340
|View full text |Cite
|
Sign up to set email alerts
|

Student-led rehabilitation groups and clinics in entry-level health education: a scoping review

Abstract: Student-led rehabilitation groups and clinics in entry-level health education: a scoping review AbstractObjective: The purpose of this review was to identify, map, and describe the characteristics of student-led physical rehabilitation groups and clinics in entry-level health education. Introduction:Student-led groups and clinics for physical rehabilitation are an emergent phenomenon in entry-level health professional education. Data gathered in this scoping review aimed to provide an understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
1
22
0
1
Order By: Relevance
“…Known as student‐run, student‐led groups or clinics, 2 hereafter referred to as SLCs, such services undertake a mode of delivery whereby students take primary responsibility for the operational delivery of healthcare 3 . This may be in the form of a clinic or a group, 4 or as a health intervention, for example, for those with cardiovascular disease 5 . Delivered in a uni or interprofessional format for pre‐registration health professionals, a recent scoping review found that the aims of SLCs for pre‐registration education included enhancing the curriculum, providing clinical placement hours, which can be included as part of degree requirements, or for altruistic reasons 4 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Known as student‐run, student‐led groups or clinics, 2 hereafter referred to as SLCs, such services undertake a mode of delivery whereby students take primary responsibility for the operational delivery of healthcare 3 . This may be in the form of a clinic or a group, 4 or as a health intervention, for example, for those with cardiovascular disease 5 . Delivered in a uni or interprofessional format for pre‐registration health professionals, a recent scoping review found that the aims of SLCs for pre‐registration education included enhancing the curriculum, providing clinical placement hours, which can be included as part of degree requirements, or for altruistic reasons 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This may be in the form of a clinic or a group, 4 or as a health intervention, for example, for those with cardiovascular disease 5 . Delivered in a uni or interprofessional format for pre‐registration health professionals, a recent scoping review found that the aims of SLCs for pre‐registration education included enhancing the curriculum, providing clinical placement hours, which can be included as part of degree requirements, or for altruistic reasons 4 . Other reported aims include providing a service for population health and well‐being 6 and promoting social enterprise 7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier reviews have examined the learning outcomes that result for students involved in such clinics. 13–15 Smaller-scale reviews have also been published on health outcomes specifically for SRC patients with cardiovascular disease or risk factors 16 and on student-delivered care in a physical rehabilitation context, 17 but the totality of evidence related to patient outcomes for patients in SRCs has not yet been systematically explored. Seeking to address this gap in knowledge, this integrative review aims to synthesize literature evaluating clinical patient outcomes of SRCs.…”
Section: Introductionmentioning
confidence: 99%